2010
DOI: 10.1111/j.1365-2141.2010.08127.x
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of the MEK/ERK signalling cascade by AS703026, a novel selective MEK1/2 inhibitor, induces pleiotropic anti‐myeloma activity in vitro and in vivo

Abstract: Summary This study investigated the cytotoxicity and mechanism of action of AS703026, a novel, selective, orally bioavailable MEK1/2 inhibitor, in human multiple myeloma (MM). AS703026 inhibited growth and survival of MM cells and cytokine‐induced osteoclast differentiation more potently (9‐ to 10‐fold) than AZD6244. Inhibition of proliferation induced by AS703026 was mediated by G0‐G1 cell cycle arrest and was accompanied by reduction of MAF oncogene expression. AS703026 further induced apoptosis via caspase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
91
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(95 citation statements)
references
References 36 publications
3
91
0
1
Order By: Relevance
“…2,4,5 Among the signaling pathways involved in the regulation of cell survival are members of the mitogen-activated protein kinase (MAPK) family, which includes three members: extracellular-regulated kinase (ERK1/2), Jun N-terminal kinase (JNK) and p38-MAPK signaling. [6][7][8] While the functions of ERK1/2 and p38-MAPK in MM have been defined in recent studies, 9,10 the role of JNK in the pathogenesis of the disease is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…2,4,5 Among the signaling pathways involved in the regulation of cell survival are members of the mitogen-activated protein kinase (MAPK) family, which includes three members: extracellular-regulated kinase (ERK1/2), Jun N-terminal kinase (JNK) and p38-MAPK signaling. [6][7][8] While the functions of ERK1/2 and p38-MAPK in MM have been defined in recent studies, 9,10 the role of JNK in the pathogenesis of the disease is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…17,19,20 In vitro OC culture and determination of OC formation CD14 ϩ OC precursor cells were selected by monocyte-cell enrichment RS cocktail (StemCell Technologies) from peripheral blood mononuclear cells from normal donors or MM patients after informed consent. 17,20 They were seeded in 96-well plates at 5 ϫ 10 4 cells per well on plastic or 1.5 ϫ 10 5 cells per well on dentine discs with DMEM/10% FCS supplemented with RANKL (50 ng/mL; PeproTech) and M-CSF (25 ng/mL; PeproTech), in the presence of serial dilutions of PCI-32765 (0-10M; Pharmacyclics). OCs were identified by staining for tartrateresistant acid phosphatase activity (TRAP), according to the manufacturers' instructions (Sigma-Aldrich).…”
Section: Cell Lines and Patient Sample Processingmentioning
confidence: 99%
“…[8][9][10] A novel, potent inhibitor of MEK1/2 affected MAF protein levels in the MM cell line H929. 11 We now extend these findings to a larger panel of MM cell lines to investigate whether particular myeloma subtypes would be especially sensitive to MEK inhibition. The current study dissects the contribution of MEK/ERK/AP-1 signaling to the transcription of MAF in MM.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies with MM cells have also found caspase 3-dependent apoptosis in MM cells after MEK inhibition. 11,28 It is possible that the G 1 arrest was seen predominantly in the K-RAS mutant cell lines that are dependent on MEK signaling, whereas the MAF-expressing cells are more driven to apoptosis. In our hands and others, MEK inhibition induced myeloma cell apoptosis despite the presence of supportive contact with bone marrow stromal cells.…”
mentioning
confidence: 99%